Proteomic Profiling of Venoms from Bungarus suzhenae and B. bungaroides: Enzymatic Activities and Toxicity Assessment - Chenying Yang; Li Ding; Qiyi He; Xiya Chen; Haiting Zhu; Feng Chen; Wanzhou Yang; Yuexin Pan; Zhiyuan Tai; Wenhao Zhang; Zeyuan Yu; Zening Chen; et al. (Toxins)
Kraits are venomous snakes of the genus Bungarus from the family Elapidae. Their venom typically demonstrates neurotoxicity; however, the toxicity is significantly influenced by the snake’s species and geographical origin. Among the Bungarus species, Bungarus suzhenae and B. bungaroides have been poorly studied, with little to no information available regarding their venom composition. In this study, a proteomic approach was employed using LC-MS/MS to identify proteins from trypsin-digested peptides. The analysis revealed 102 venom-related proteins from 18 distinct functional protein families in the venom of B. suzhenae, with the primary components being three-finger toxins (3-FTx, 25.84%), phospholipase A2 (PLA2, 40.29%), L-amino acid oxidase (LAAO, 10.33%), Kunitz-type serine protease inhibitors (KUN, 9.48%), and snake venom metalloproteinases (SVMPs, 6.13%). In the venom of B. bungaroides, 99 proteins from 17 families were identified, with primary components being 3-FTx (33.87%), PLA2 (37.91%), LAAO (4.21%), and KUN (16.60%). Enzymatic activity assays confirmed the presence of key venom enzymes. Additionally, the LD50 values for B. suzhenae and B. bungaroides were 0.0133 μg/g and 0.752 μg/g, respectively, providing a reference for toxicity studies of these two species. This research elucidates the proteomic differences in the venoms of these two species, offering a foundation for developing antivenoms and clinical treatments for envenomation.